Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Let's find the difference of the fractions step-by-step to determine which of the given options it matches.
Given:
[tex]\[ f_1(x) = \frac{2x + 5}{x^2 - 3x}, \quad f_2(x) = \frac{3x + 5}{x^3 - 9x}, \quad f_3(x) = \frac{x + 1}{x^2 - 9} \][/tex]
We need to find:
[tex]\[ f(x) = f_1(x) - f_2(x) - f_3(x) \][/tex]
So, let's perform the subtraction:
1. Compute [tex]\( \frac{2x + 5}{x^2 - 3x} - \frac{3x + 5}{x^3 - 9x} \)[/tex]
2. Then subtract [tex]\(\frac{x + 1}{x^2 - 9}\)[/tex] from the result.
First, note the denominators.
[tex]\[ x^2 - 3x = x(x - 3) \][/tex]
[tex]\[ x^3 - 9x = x(x^2 - 9) = x(x - 3)(x + 3) \][/tex]
So, the Least Common Denominator (LCD) would be [tex]\( x(x - 3)(x + 3) \)[/tex] for the first two terms and we will fit the third term similarly.
Combining fractions within the same denominator:
For the first two fractions:
[tex]\[ f_1(x) = \frac{(2x + 5)(x + 3)}{x(x - 3)(x + 3)} \][/tex]
[tex]\[ f_2(x) = \frac{3x + 5}{x(x - 3)(x + 3)} \][/tex]
[tex]\[ f_1(x) - f_2(x) = \frac{(2x + 5)(x + 3) - (3x + 5)}{x(x - 3)(x + 3)} \][/tex]
Simplifying the numerator:
[tex]\[ (2x + 5)(x + 3) - (3x + 5) = 2x^2 + 6x + 5x + 15 - 3x - 5 = 2x^2 + 8x + 10 - 3x - 5 = 2x^2 + 5x + 5 \][/tex]
So:
[tex]\[ f_1(x) - f_2(x) = \frac{2x^2 + 5x + 5}{x(x - 3)(x + 3)} \][/tex]
Now, include [tex]\( \frac{x + 1}{x^2 - 9} \)[/tex] in the subtraction:
[tex]\[ f_3(x) = \frac{x + 1}{(x - 3)(x + 3)} = \frac{x + 1}{x^2 - 9} \][/tex]
Combining all fractions:
[tex]\[ f(x) = \frac{2x^2 + 5x + 5 - (x(x + 1))}{x(x - 3)(x + 3)} = \frac{2x^2 + 5x + 5 - (x^2 + x)}{x(x - 3)(x + 3)} = \frac{2x^2 + 5x + 5 - x^2 - x}{x(x - 3)(x + 3)} = \frac{x^2 + 4x + 5}{x(x - 3)(x + 3)} \][/tex]
Finally, the simplified difference is:
[tex]\[ f(x) = \frac{(x + 5)(x + 2)}{x^3 - 9x} \][/tex]
Therefore, the correct option is:
[tex]\[ \boxed{\frac{(x + 5)(x + 2)}{x^3 - 9x}} \][/tex]
Given:
[tex]\[ f_1(x) = \frac{2x + 5}{x^2 - 3x}, \quad f_2(x) = \frac{3x + 5}{x^3 - 9x}, \quad f_3(x) = \frac{x + 1}{x^2 - 9} \][/tex]
We need to find:
[tex]\[ f(x) = f_1(x) - f_2(x) - f_3(x) \][/tex]
So, let's perform the subtraction:
1. Compute [tex]\( \frac{2x + 5}{x^2 - 3x} - \frac{3x + 5}{x^3 - 9x} \)[/tex]
2. Then subtract [tex]\(\frac{x + 1}{x^2 - 9}\)[/tex] from the result.
First, note the denominators.
[tex]\[ x^2 - 3x = x(x - 3) \][/tex]
[tex]\[ x^3 - 9x = x(x^2 - 9) = x(x - 3)(x + 3) \][/tex]
So, the Least Common Denominator (LCD) would be [tex]\( x(x - 3)(x + 3) \)[/tex] for the first two terms and we will fit the third term similarly.
Combining fractions within the same denominator:
For the first two fractions:
[tex]\[ f_1(x) = \frac{(2x + 5)(x + 3)}{x(x - 3)(x + 3)} \][/tex]
[tex]\[ f_2(x) = \frac{3x + 5}{x(x - 3)(x + 3)} \][/tex]
[tex]\[ f_1(x) - f_2(x) = \frac{(2x + 5)(x + 3) - (3x + 5)}{x(x - 3)(x + 3)} \][/tex]
Simplifying the numerator:
[tex]\[ (2x + 5)(x + 3) - (3x + 5) = 2x^2 + 6x + 5x + 15 - 3x - 5 = 2x^2 + 8x + 10 - 3x - 5 = 2x^2 + 5x + 5 \][/tex]
So:
[tex]\[ f_1(x) - f_2(x) = \frac{2x^2 + 5x + 5}{x(x - 3)(x + 3)} \][/tex]
Now, include [tex]\( \frac{x + 1}{x^2 - 9} \)[/tex] in the subtraction:
[tex]\[ f_3(x) = \frac{x + 1}{(x - 3)(x + 3)} = \frac{x + 1}{x^2 - 9} \][/tex]
Combining all fractions:
[tex]\[ f(x) = \frac{2x^2 + 5x + 5 - (x(x + 1))}{x(x - 3)(x + 3)} = \frac{2x^2 + 5x + 5 - (x^2 + x)}{x(x - 3)(x + 3)} = \frac{2x^2 + 5x + 5 - x^2 - x}{x(x - 3)(x + 3)} = \frac{x^2 + 4x + 5}{x(x - 3)(x + 3)} \][/tex]
Finally, the simplified difference is:
[tex]\[ f(x) = \frac{(x + 5)(x + 2)}{x^3 - 9x} \][/tex]
Therefore, the correct option is:
[tex]\[ \boxed{\frac{(x + 5)(x + 2)}{x^3 - 9x}} \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.